Environmental and climate change in Asia : ecological footprints and green prospects - Savage, Victor R.; Lye, Lin Heng (Prentice Hall, 2011)
This collection of essays on environment and climate change within Asia is written by faculty members to mark the celebration of the 10th Anniversary (2001-2011) of the National University of Singapore's Masters in Environmental Management (MEM) program. These essays reflect the multi-disciplinary and inter-disciplinary pedagogical nature of the MEM program with academic contributions from the Arts, Architecture, Building and Real Estate, Business, Economics, Law, Medicine, and Sciences as well as inputs from industry and non-government organizations. The papers provide a mix of field-study research, grounded conceptual distillations, policy and applied eco-developmental suggestions, critical reviews of government programs, and comparisons of local and global environment and climate change interventions. This is a must-read book for any academic researcher, government official, corporate decision-maker and the informed public about the ecological impacts and outcomes, social and economic implications, and the political ramifications and state policy options in the defining 21st century of global climate change. Read it to become an informed and active participant in environmental debates and dialogues.